Zinc transport across cell membranes - Liou, C; Liou, Chen-Chen (1992)
The mechanism of zinc transport has been investigated in red cells from normal humans, lampreys, sheep, sickle cell anaemia patients and in bovine chondrocytes. In all the cell types investigated except for lamprey red cells, zinc transport is mainly via the anion exchanger (band 3), which accounts for over 80% of total measured zinc uptake, when the medium contains no zinc binding ligands. Zinc uptake via the band 3 pathway is stimulated by the presence of bicarbonate (5mM) and inhibited by treatment with DIDS or SITS (10andmu;M). This anion-dependent mechanism represents the major route for zinc transport across the cell membrane in vitro. The presence of the zinc binding ligands albumin and histidine in the media greatly reduced the uptake of zinc via the anion exchanger due to the decrease in free zinc concentration. Histidine, in addition to its chelating effect, shows a specific facilitating effect on zinc uptake in all the cell types. This stimulating effect of histidine was stereospecific (significantly different between L-, and D-histidine) in red cells from normal humans and sickle cell anaemia patients, but not in red cells from lampreys, sheep, and bovine chondrocytes. Evidence from all cell types strongly suggests that the stimulus is due to the cotransport of zinc and histidine via the histidine transport systems, which are system L, and y* in normal human and sickle red cells; a non-stereospecific L-like system in lamprey red cells and bovine chondrocytes; system C or unknown specific histidine transporter in sheep red cells. The amino acid linked zinc uptake may represent a physiologically significant mechanism for zinc transport into cells.